Analysis of Mental Disorders of Aggression in Students (Case Study of Class X IPS 4 at Mujahidin Private High School Pontianak) - Astari, Zuri; Zatalini, Adhalia; Daniel, Daniel (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
Aggressive behavior among adolescents, especially high school students, has become a significant issue today. This article presents an analysis of deviant aggressive behavior among students in class XI IPS 4 at SMA Swasta Mujahidin Pontianak, covering the forms of behavior, causes, impacts, and efforts to address aggressive behavior among students. The aim of this article is to provide a factual overview using a descriptive qualitative approach through interviews and documentation with students at SMA Swasta Mujahidin Pontianak. The interview results indicate that aggressive behavior at SMA Swasta Mujahidin Pontianak can take the form of fighting, mocking friends, bullying, or taking friends' belongings. The causes of aggressive behavior are diverse, including family influence, unpleasant conditions created by parents, a toxic peer environment, and frequent exposure to aggressive scenes. The impact of aggressive behavior can affect emotional development and academic performance. To address aggressive behavior, the school has undertaken various efforts by providing counseling services through the school counselor and implementing policies such as sanctions for the perpetrators. Aggressive behavior must be eradicated in the school environment as it is harmful and detrimental to others.